Symbiosis islands of Loteae-nodulating Mesorhizobium comprise three radiating lineages with concordant nod gene complements and nodulation host-range groupings. - Perry, Benjamin J; Sullivan, John T; Colombi, Elena; Murphy, Riley JT; Ramsay, Josh; Ronson, Clive W (Microbiology Society, 2020)
© 2020 The Authors